Pelestarian Tradisi dan Budaya Pela Gandong bagi Pencegahan Konflik Sosial di Kota Ambon - C Elly Kumari Tjahya Putri (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2014)
Social conflicts and collective violence interethnic rife in various regions in Indonesia, including Ambon city. Considering the existence of local wisdom called pela gandong (norms or values of a tradition that upholds the values of social solidarity), it was such an irony that Ambon city residents involved in violence ang amok. This situation call for an examination of the causes of such a social conflict. Social conflict caused many casualties. In order to uncover the role of pela gandong in fostering social soldarity attitudes among Ambon city residents post conflict, a research on â€œPreservation of Pela Gandong Tradition and Culture for Social Conflict Prevention in Ambon Cityâ€ had been conducted applying survey and case methods. This study led to the founding that the cause of social conflict in Ambon city is due to increasing migration flows which impacting the increasing number of unemployment in the city of Ambon. Migrant or immigrants can not readily adjust to the culture of the natives which in turn cultivate an attitude of mutual suspicion between them. Along with modernization, decreasing authority of social institutions accompanied by increasing waning of traditional values (pela gandong) primarily among young people make people easily negatively provoked by various parties. But postâ€“conflict there occurs associative, acculturation, accomodation, assimilation processes in public life as can be seen from the high attitude of social solidarity posed. For the prevention of social conflicts in the future it is recomended to develop social capital and to strengthen social insitutions to preserve traditional institutions and also to held dialogues in both horizontal and vertical dimension.